1975
DOI: 10.1177/000348947508400609
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Incision as a Contributing Factor to Tracheal Stenosis: An Experimental Study

Abstract: Tracheostomies were performed on 25 mongrel dogs, employing either a vertical or inverted U flap incision in the trachea. Following cannulation for 14 days, the animals were maintained for three months and endolarygeal photographs were taken. At the time of autopsy, comparisons of the gross specimens were carried out, as well as histological sectioning through the tracheal stomal area. Both endolaryngeal examination and study of the gross specimens at autopsy revealed less distortion of the tracheal lumen foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

1978
1978
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
1
15
1
Order By: Relevance
“…In contrast to previous animal studies comparing different types of tracheal incision, which showed either that the vertical incision should be the incision of choice [18] or that the inferior flap tracheostomy should be favorized [17,20], it is our opinion that the type of tracheal incision is relatively insignificant concerning the occurrence of clinically relevant postoperative tracheal stenosis.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In contrast to previous animal studies comparing different types of tracheal incision, which showed either that the vertical incision should be the incision of choice [18] or that the inferior flap tracheostomy should be favorized [17,20], it is our opinion that the type of tracheal incision is relatively insignificant concerning the occurrence of clinically relevant postoperative tracheal stenosis.…”
Section: Discussioncontrasting
confidence: 87%
“…Vertical tracheal incision [17][18][19] and creation of inferiorly [17,18,20] or superiorly [19] based tracheal flaps in animal models have also been studied. The incidence of late complications related to the stoma or tracheal lesions such as tracheal stenosis, formation of granulation tissue, suprastomal collapse, or fatal complications could not clearly be related to the type of tracheal incision or the creation of a tracheal flap [21,22].…”
mentioning
confidence: 99%
“…The use of PVC tubes and low pressure 'floppy' cuffs has greatly diminished the risk of tracheal injury after prolonged intubation by either route (Cooper and Grillo, 1972;Crawley and Cross, 1975) and stenosis is most likely to occur at the site of the stoma after tracheostomy (Friman et al, 1976), particularly if this has been carelessly or incorrectly fashioned (Lulenski and Batsakis, 1975). In this situation, where the trachea is already abnormal and possibly distorted, endotracheal intubation, if possible, is to be preferred.…”
Section: Munugementmentioning
confidence: 99%
“…Several types of tracheostomy incisions in dogs, including transverse and vertical, U-shaped flap through two tracheal rings, and excision of 1 cm segments of 1 and 2 rings have been compared [5,6,8,16,17,22]. Vertical tracheostomy shows the most consistent healing [5,6].…”
Section: Stomal Complicationsmentioning
confidence: 99%
“…However, tracheotomy and tracheal stoma intubation present noteworthy hazards and complications. Some of the more common complications include tracheal stenosis secondary to cuffed endotracheal tube inflation [2][3][4][20][21][22], pneumonia [10,14], tracheobronchitis [13,14], tracheitis [11], hemorrhage from innominate artery dissection [9,24], laryngeal trauma including laryngeal nerve damage [14], stoma occlusion [14], stoma closure [12][13][14], and tracheoesophageal fistula [23,24].…”
Section: Introductionmentioning
confidence: 99%